Hydraulic Structures as a Key Component of Sustainable Water Management at the Catchment Scale—Case Study of the Rgilewka River (Central Poland) - Bogumił Nowak; Mariusz Ptak; Jan Bartczak; Mariusz Sojka (Buildings, 2022)
Poland is among the European countries with the lowest water resources. The central part of Poland features the least water resources in the country. In this region, proper water management is particularly critical to maintaining high agricultural productivity. The objective of this study was to present the effects of the restoration of hydrotechnical infrastructure in the Rgilewka River catchment in the zone of the greatest water deficits. This paper analyses the effects of such works on water resources and their management. The catchment featured seven weirs in 2014, all built in the 1950s. Due to the lack of maintenance and ongoing renovation, they have lost their basic functions. In 2014, modernisation of the system commenced by rebuilding all the existing weirs. Two new weirs were also constructed. The work was completed in 2021. The currently existing weirs provide greater water retention and management capabilities. The direct impact of weirs ranges from 1.9 to 3.5 ha, their indirect impact from 34 to 70 ha, and the river channel retention varies from 2200 to 5400 m3. Total water retention in the Rgilewka River channel due to the modernisation of hydrotechnical infrastructure reaches 25,400 m3. The direct (total) impact range will cover an area of 16.4 ha, and the indirect impact range an area of 284 ha.